Alternatives in Molecular Diagnostics of Encephalitozoon and Enterocytozoon Infections - Alexandra Valenčáková; Monika Sučik (Journal of Fungi, 2020)
Microsporidia are obligate intracellular pathogens that are currently considered to be most directly aligned with fungi. These fungal-related microbes cause infections in every major group of animals, both vertebrate and invertebrate, and more recently, because of AIDS, they have been identified as significant opportunistic parasites in man. The Microsporidia are ubiquitous parasites in the animal kingdom but, until recently, they have maintained relative anonymity because of the specialized nature of pathology researchers. Diagnosis of microsporidia infection from stool examination is possible and has replaced biopsy as the initial diagnostic procedure in many laboratories. These staining techniques can be difficult, however, due to the small size of the spores. The specific identification of microsporidian species has classically depended on ultrastructural examination. With the cloning of the rRNA genes from the human pathogenic microsporidia it has been possible to apply polymerase chain reaction (PCR) techniques for the diagnosis of microsporidial infection at the species and genotype level. The absence of genetic techniques for manipulating microsporidia and their complicated diagnosis hampered research. This study should provide basic insights into the development of diagnostics and the pitfalls of molecular identification of these ubiquitous intracellular pathogens that can be integrated into studies aimed at treating or controlling microsporidiosis.